Exosome-based crosstalk in glaucoma pathogenesis: a focus on oxidative stress and neuroinflammation - Wang, Lixiang; Wei, Xin (Frontiers in Immunology, 2023)
Exosomes are membrane-bound tiny particles that are released by all live cells that contain multiple signal molecules and extensively participate in numerous normal physical activities and pathologies. In glaucoma, the crucial role of exosome-based crosstalk has been primarily revealed in animal models and ex vivo cell studies in the recent decade. In the aqueous drainage system, exosomes derived from non-pigment ciliary epithelium act in an endocrine manner and specifically regulate the function of the trabecular meshwork to cope with persistent oxidative stress challenges. In the retina, a more complicated regulatory network among microglia, retinal neurons, retinal ganglial cells, retinal pigment epithelium, and other immune effector cells by exosomes are responsible for the elaborate modulation of tissue homeostasis under physical state and the widespread propagation of neuroinflammation and its consequent neurodegeneration in glaucoma pathogenesis. Accumulating evidence indicates that exosome-based crosstalk depends on numerous factors, including the specific cargos they carried (particularly micro RNA), concentration, size, and ionization potentials, which largely remain elusive. In this narrative review, we summarize the latest research focus of exosome-based crosstalk in glaucoma pathogenesis, the current research progress of exosome-based therapy for glaucoma and provide in-depth perspectives on its current research gap.